(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Political power as a social phenomenon is the most interesting subject of scientific interests of scientists from all over the world. In the conditions of modernity it is important to understand what origins the concept of political power has in terms of science, and how noticeable were the changes through which this concept has passed from the times of antiquity to the present day. A significant area of research has been tested by the research works of scientists in terms of history, ethnography, ethno-politics, as well as philosophy and law, and only a small amount is related to the field of political science. In this context, this article considers the formation of political power through the prism of history, as well as its role in modern conditions of innovation and technological process, which covers large socially significant and socio-political spheres in the life of society.